Risky Mortgages and Macroprudential Policy: A Calibrated DSGE Model for Lithuania - Karmelavičius, Jaunius (Ekonomika, 2021)
Following the financial crisis of 2009 there was an emergence of macroprudential policy tools, as well as a need to model the macroeconomy and the financial sector in a coherent framework. This paper develops and calibrates a small open economy DSGE model for Lithuania to shed some light on the interactions between the macroeconomy and the banking sector, regulated by macroprudential policy. The model features housing market, and endogenous credit risk a la de Walque et al. (2010), whereby the household can default on mortgage repayments, what leads to housing collateral seizure. Foreign-owned banks, that are subject to risk-sensitive macroprudential capital requirements, take into account not only the mortgage default rate but also the cap on loan to value (LTV) ratio when making lending decisions. Using this mechanism, we show that while a more stringent LTV constraint reduced credit demand, it can also lead to an expansion in credit supply via lower credit risk. Therefore, a tightening of LTV requirement should result in only a slight reduction in mortgage lending, coupled with lower interest rate margins. The article compares the impact of the tightening of three macroprudential tools, namely, bank capital requirements, mortgage risk weights and LTV limit. We find that broad-based capital requirements, such as the counter-cyclical capital buffer, are less efficient in leaning against the housing credit cycle, because of a relatively large cost incurred on the firm sector.
Keywords: macroprudential policy; mortgage defaults; LTV; capital requirements